The Influencer of Perceived Ease of Use, Perceived Risk, and Locus of Control on the Financial Behavior of Fintech Lending Users - Akbar Nur Ramadhan; Dasra Viana, Eka (GREENOMIKA, 2023)
Along with the development of current technological advances, innovations have emerged in the financial sector that provide online loan services and are called fintech lending. The behavior of borrowing money has also shifted from offline to online due to the convenience features provided during the loan process. This change in behavior can be an opportunity for online loan service providers to making strategies to increase fintech lending users. Therefore, this study aims to examine the effect of perceived ease of use, perceived risk, and locus of control on the financial behavior of fintech lending users. The determination of the sample was carried out using a non-probability sampling technique with a purposive sampling method. The data analysis method used is descriptive analysis technique and SEM-PLS. The results of the analysis show that the perceived ease of use and locus of control variables have a positive and significant effect on financial behavior, while the perceived risk variable does not have a significant effect on the financial behavior of generation Z in fintech lending users in Jabodetabek.